Evaluation of Return to Sport and Anxiety in Injured Team Athletes: A Mixed Methods Study - Serdar Kocaekşi; Serap Cavkaytar; Canan Turgut (Pamukkale Spor Bilimleri Dergisi)
This study aimed to evaluate the return to sport and anxiety in athletes with anterior cruciate ligament injury. It was conducted using an exploratory sequential mixed design in mixed methods research. In the first phase of the study, 185 athletes (87 women and 98 men) with anterior cruciate ligament injuries were included in the quantitative dimension. In the qualitative dimension, semi-structured interviews were conducted with 18 athletes. In the quantitative and qualitative findings obtained, significant differences were obtained in terms of the return to sport and anxiety states of athletes with an anterior cruciate ligament injury in terms of the branch, league level, duration of return to sport, and age variables. Qualitative findings were used to support the results obtained from quantitative data. At this point, in the qualitative findings, the anxiety experienced by the athletes was very high. They emphasized that the change in the league level did not affect the process of return to sport. It was reported that athletes feared re-injury on return and were concerned that they would not be able to return to their previous performance. In other results related to qualitative findings, the importance of positive social support and physiotherapy support for injured athletes was emphasized. In their opinions about psychological support during the injury process, it was stated that psychological support is important for athletes in this process and that support should be obtained from expert sports psychologists, especially if needed.